The role of technology in business-to-consumer e-commerce: Evidence from Asia - Jong Woo Kang; Tengfei Wang; Dorothea Ramizo (Asian Development Bank (ADB), 2021)
The business-to-consumer (B2C) online commerce landscape is changing rapidly, supported by the technological innovation. However, its diffusion remains concentrated in developed and large economies and is creating a digital divide that excludes small and medium-sized enterprises and people with limited means. The coronavirus disease (COVID-19) pandemic exposed an urgent need to close the divide, both within and across countries. This paper explores disparities in B2C online commerce revenues among selected Asian economies by investigating the role of technology adoption in B2C sales online. Using proprietary panel data to ensure comparability of B2C online commerce across countries and years, the study investigates empirically the possible drivers of B2C online commerce growth. This paper yields important insights for policy makers and businesses and provides evidence that internet access and speed, online security, and financial inclusiveness matter in facilitating internet retail sales. Governments should consider these as important issues in building an enabling environment that will help B2C online commerce adapt to the post COVID-19 world and ensure that innovations create opportunities for all.
Keywords: F13; F14; 330; broadband; e-commerce; financial inclusion; technology